Beginning Silverlight 2 - Lair, Robert (Apress, 2012)
This book is written for application developers who want to get started with Silverlight 2. It assumes that you have some experience developing applications using technologies related to Microsoft’s ASP.NET, and have worked with Microsoft Visual Studio. You should be familiar with the JavaScript, C#, and XML languages.